(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The present study was conducted to relationship in job satisfaction and teacher effectiveness between Government school and Private school teachers of Haryana. The data pertaining to this study was collected on 50 Government school and 50 Private school of different parts of Haryana by using the Teacher Effectiveness Scale by Dr. KUMAR AND MUTHA (1974) and Job satisfaction scale by Dr. PARMOD KUMAR AND D.N MUTHA(1993) and the response in YES/NO form were converted numerically following the scoring keys. The collected data were analyzed statistically through Mean, Standard Deviation (S.D) & Correlation , T-test and the level of significant was observed at 0.05 level of confidence. On the basis of statistical findings it was conclude that there were no significant relationship between Teacher Effectiveness and Job satisfaction of male teachers and female teacher (t0.05 (98) 252.246 & 21.1) 256.72 & 18.42.There were present the relationship between Teacher Effectiveness and job satisfaction of Govt. School secondary teachers and Private school secondary teacher. The calculated mean of Teacher Effectiveness and job satisfaction is (242.46& 20.16)( 262.38&19.56 ) respectively there were significant relationship between Teacher Effectiveness and job satisfaction.